SPE Improved Oil Recovery Conference 2016
DOI: 10.2118/179575-ms
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Guidelines for the Application of In-Situ Polymer Gels for Injection Well Conformance Improvement Based on Field Projects

Abstract: Polymer gels are increasingly applied to improve sweep efficiency of different IOR/EOR recovery processes. Three in-situ polymer gel systems including bulk gels, colloidal dispersion gels, and weak gels are often used to mitigate water production caused by reservoir heterogeneity and unfavorable mobility ratio of oil and injected fluids. Selecting the most appropriate gel system is a key component for a successful conformance improvement treatment. Screening criteria in terms of reservoir and fluid characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…A previous study suggested that the CDG can tolerate a water salinity up to 30,000 mg/l without any problems [6]. However, a recent screening criteria suggested that CDG could tolerate between 3,000 mg/l to 130,000 mg/l of water salinity in the field applications [52]. Hence, in order to demonstrate the effect of salinity on CDG, the effect of salinity on the viscosity of HPAM polymer solution should be investigated.…”
Section: Effect Of Salinity On the Performance Of Cdgmentioning
confidence: 99%
“…A previous study suggested that the CDG can tolerate a water salinity up to 30,000 mg/l without any problems [6]. However, a recent screening criteria suggested that CDG could tolerate between 3,000 mg/l to 130,000 mg/l of water salinity in the field applications [52]. Hence, in order to demonstrate the effect of salinity on CDG, the effect of salinity on the viscosity of HPAM polymer solution should be investigated.…”
Section: Effect Of Salinity On the Performance Of Cdgmentioning
confidence: 99%
“…Thus, hydrogel nanocomposites have been widely studied because it has better properties compared to conventional ones. In addition, hydrogel nanocomposites present better thermal and mechanical stabilities, which improve the oil recovery efficiency. , …”
Section: Introductionmentioning
confidence: 99%
“…[6] These systems are injected into a reservoir formation with the purpose of reducing water production, diverting it to areas not previously crossed with higher oil saturation. [7,8] Polymeric gels can be hydrophilic, soft, and semisolid systems derived from polymers that form a threedimensional network structure that swells in the presence of water. [9] One way to use gel systems for conformance control is through pre-formed particles, which are easily prepared at the surface with polymer and crosslinkers before being injected into the target reservoir.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Nevertheless, because of the soft and fragile nature of hydrogels, studies have focused on developing new polymeric hydrogels reinforced with fillers that have improved mechanical properties. [8,11] Numerous studies with different fillers exist, among them silica, [12,13,14,15] clay, [16,17,18] and coal fly ash (CFA). [19,20,21] CFA is a fine particle from the combustion of pulverized coal in power plants.…”
Section: Introductionmentioning
confidence: 99%